An investigation into the critical ingredients of intensive support teams for adults with intellectual disabilities who display challenging behaviour - Lucretia Thomas; Brynmor Lloyd-Evans; Louise Marston; Angela Hassiotis (BJPsych Bulletin)
Aims and method NHS England recommends the commissioning of intensive support teams (ISTs) to provide effective support to people with intellectual disability (ID) when in crisis. However, there is a paucity of evidence regarding how these services should be organised. This exploratory secondary analysis of data from the IST-ID study aimed to investigate IST characteristics that relate to clinical outcomes. The primary outcome was mean change in the total score on the Aberrant Behavior Checklist and its subscales.